2014
DOI: 10.1111/eea.12197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Drosophila suzukii immunomarking for mark‐capture research

Abstract: Drosophila suzukii Matsumura (Diptera: Drosophilidae) utilizes ‘Himalaya’ blackberry, Rubus armeniacus Focke (Rosaceae), as a host and may invade berry and stone fruit crops from field margins containing this invasive weed. Laboratory and semi‐field studies were conducted to determine (1) the persistence of protein marks including 10% chicken egg whites (egg albumin protein), 20% bovine milk (milk casein protein), and 20% soy milk (soy trypsin inhibitor protein) on topically sprayed D. suzukii, (2) protein ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Klick et al. () also showed high variability in protein acquisition by spotted wing drosophila, Drosophila suzukii Matsumura, exposed to protein‐treated blackberry leaf tissue. That study reported that flies rapidly acquired and retained egg white, but not bovine milk and soy milk markers.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Klick et al. () also showed high variability in protein acquisition by spotted wing drosophila, Drosophila suzukii Matsumura, exposed to protein‐treated blackberry leaf tissue. That study reported that flies rapidly acquired and retained egg white, but not bovine milk and soy milk markers.…”
Section: Discussionmentioning
confidence: 97%
“…; Klick et al. ). However, if three marks are needed for a particular study, our data suggest that we could mark about 90% of the resident target population with a 10, 66 and 33% concentration of egg white, bovine milk and soy milk, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…. These habitats may play an important role for the population dynamics of D. suzukii as they can serve as reservoirs for the recolonization of crops after the application of insecticides and provide shelter for the flies during unfavourable weather conditions4546. Further studies are required to investigate their relative importance for D. suzukii and the community of potential natural enemies to assess the impact of management actions.…”
Section: Discussionmentioning
confidence: 99%